2021
DOI: 10.1111/1759-7714.13839
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibition overcomes EGFR amplification‐induced resistance to third‐generation EGFR‐TKIs

Abstract: Background Patients with non‐small cell lung cancer (NSCLC) harboring activating EGFR mutations are sensitive to epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKIs) but inevitably develop resistance to the inhibitors mostly through acquisition of the secondary T790M mutation. Although third‐generation EGFR‐TKIs overcome this resistance by selectively inhibiting EGFR with EGFR‐TKI‐sensitizing and T790M mutations, acquired resistance to third‐generation EGFR‐TKIs invariably develops. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Benzimidazole (1) was treated with 4-bromo-3oxobutanenitrile in presence of a base such as Cs 2 CO 3 in acetonitrile and gave 4-(1H-benzo[d]imidazol-1-yl)-3oxobutanenitrile (2). The obtained compound was reacted with hydroxylamine sulfate under basic conditions (pH 7-8) to produce aryl amine (3). Finally, the intermediate 3 was treated with several aromatic carboxylic acids in presence of coupling agents such as EDCI and HOBt in dichloromethane to give the corresponding amides 4a-4m with high yields (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzimidazole (1) was treated with 4-bromo-3oxobutanenitrile in presence of a base such as Cs 2 CO 3 in acetonitrile and gave 4-(1H-benzo[d]imidazol-1-yl)-3oxobutanenitrile (2). The obtained compound was reacted with hydroxylamine sulfate under basic conditions (pH 7-8) to produce aryl amine (3). Finally, the intermediate 3 was treated with several aromatic carboxylic acids in presence of coupling agents such as EDCI and HOBt in dichloromethane to give the corresponding amides 4a-4m with high yields (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Isoxazole derivatives are used as adaptable building blocks in synthesis of anticancer agents [1]. For example, resorcinyl 4,5-diarylisoxazole amides was developed as a potent heat shock protein (HSP90) inhibitor (NVP-AUY922 (Luminespib)) [2], was active against a variety of tumor xenografts, and has been evaluated in phase II clinical trials [3]. Isoxazole derivatives of comberastatin A-4 analogues were described as tubulin polymerization inhibitors with anti-proliferative activity towards various cellines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“… 36 Additionally, as a class of proteins of interest and relevance to tumor growth, HSP90 has been shown in previous in vitro and vivo studies to be effective in inhibiting the proliferation of lung adenocarcinoma cells with EGFR mutations or ALK-rearranged. In the study by Piotrowska et al, 37 a total of 29 patients with EGFR-mutated lung adenocarcinoma were included, with an ORR of 17% and a median OS of 13 months after treatment with an HSP90 inhibitor. In a study by Sang et al, 38 it was first demonstrated in vitro that hsp90 inhibitors in non-adenocarcinoma cell lines with ALK rearrangement could inhibit cell proliferation in a gradient manner and that EGFR and ALK expression levels in the cell lines were subsequently reduced.…”
Section: Discussionmentioning
confidence: 99%